Components of Tourist Attraction in Ubari (Journal of human and social sciences, 2023)
It is almost self-evident that Libya is one of the world's most important tourist destinations, endowed with human and natural components capable of competing in global tourism. Since these tourist components form the very foundation of tourism, it is imperative to provide all supporting capabilities for tourist activity and to prepare conditions that ensure the optimal reception for waves of tourists arriving from all corners of the world during the annual tourist seasons. Thus, the core problem can be summarized in the vandalism of these tourist landmarks (antiquities of various types) contrasted with a lack of concern from officials regarding this issue. As long as this heritage remains neglected, it is necessary to highlight some of the problems it suffers from, in the hope that they will find a listening ear. Needless to say, the importance of this study stems from its aim to identify the spatial characteristics of the natural and human components in the study area.
Keywords: Tourism Attractiveness Factors; Desert Tourism; Natural and Human Resources; Archaeological Landmarks; Ubari